Natural products alleviate viral pneumonia by modulating inflammatory and oxidative-stress pathways - Tie, Yifu; Liu, Han; Zhang, Tong; Meng, Tianwei; Liang, Qun (Frontiers in Pharmacology, 2025)
Viral pneumonia, primarily caused by influenza viruses, coronaviruses, and other respiratory pathogens, is characterized by direct alveolar epithelial injury and an excessive immune response, leading to severe inflammation, oxidative stress, and, in critical cases, acute respiratory distress syndrome and multi-organ failure. Traditional Chinese Medicine (TCM), widely employed in China for both the prevention and treatment of viral pneumonia, provides multitarget and broad-spectrum therapeutic benefits with low toxicity and minimal side effects, offering a promising alternative to conventional antiviral therapies. Recent studies have demonstrated that natural products derived from TCM, including flavonoids, polyphenols, polysaccharides, and terpenoids, can effectively modulate immune and oxidative stress responses by targeting multiple signaling pathways. In this review, we conducted a systematic literature search in PubMed, Web of Science, and SciFinder databases, focusing primarily on studies published over the past decade. Keyword combinations included “viral pneumonia,” “Traditional Chinese Medicine,” “natural products,” “inflammation,” and “oxidative stress,” in addition to mechanism-related terms such as “NF-κB,” “Nrf2,” “PI3K/Akt,” “MAPK,” and “NLRP3 inflammasome.” Natural compounds acting on these pathways have been shown to suppress cytokine storms, reduce reactive oxygen species accumulation, preserve alveolar epithelial integrity, and alleviate pulmonary inflammation. This review highlights the latest progress in understanding how natural products exert protective effects in viral pneumonia through the modulation of inflammation and oxidative stress–related pathways. These findings provide a theoretical foundation for developing novel anti-inflammatory and antioxidant therapeutic strategies based on natural medicines for the treatment of viral respiratory diseases.